The Influence Of Word-Of-Mouth Online And Celebrity Endorser On Attitudes And Intentions Of Tourists To Visit Indonesia During The Covid-19 Pandemic - Lin Lin Syah; Dedi Rianto Rahadi; M. Miftah Farid (Journal of Management and Leadership, 2021)
During the COVID-19 pandemic, many community activities were restricted, including visiting tourist destinations. This policy has an impact on the management of tourist areas experiencing losses. This study aims to examine the effect of electronic word of mouth (e-WOM), Celebrity Endorser, on the attitudes and intentions of tourists to visit West Java, Indonesia. Collecting data using a questionnaire with a sample of 180 respondents with convenience sample method The technique of data analysis using Structural Equation Modeling (SEM) of a statistical software package AMOS version 24. The conclusion from hypothesis The results show (1) e-WOM has no significant effect on tourist attitudes, (2) e-WOM has a significant effect on the intention to visit tourists. (3) celebrity endorser has a significant effect on tourist attitudes. (4) celebrity endorser has a significant effect on intentions to visit tourist attractions, (5) tourist attitudes have no significant effect on intentions to visit tourist attractions. The COVID-19 pandemic has become a momentum and taken into consideration to implement Virtual Reality Tourism as a solution before tourists decide to make a tourist visit.